A Differential Game Model of Duopoly - Clemhout, S.; Leitmann, G.; Wan, H. Y. (Econometrica, 1971)
[The present study considers two duopolists each trying to outsell the other, under a non-negative profit constraint. Both advertisement and the customer-held stocks are brought into play. The optimal behavior for the duopolists is deduced from a mathematical model of differential games.]